1996
DOI: 10.1177/44.2.8609375
|View full text |Cite
|
Sign up to set email alerts
|

Localization of apoptotic cells by direct immunogold detection of digoxigenin-labeled genomic DNA in semithin sections.

Abstract: In this study, which correlates apoptosis with avian ovarian physiology, we modified an in situ DNA nick end-labeling method using immunogold reagents to detect apoptotic cells in semithin sections of quail ovaries embedded in glycol methacrylate resin. Special attention was paid to the prevention of background staining. The results are com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Another possible factor contributing to germ cells reduction in chicken embryonic ovaries is Intarapat and Stern: Gonadal Asymmetry in Chicken Embryos apoptosis of germ cells (Ukeshima and Fujimoto, 1991;Ukeshima, 1996;Van Nassauw et al, 1996). Previous studies reported that there are numerous spaces in the medulla of embryonic ovaries called "lacunae" in which dead oogonia are eliminated from both left and right medulla through the lacunae (Romanoff, 1960;Kannankeril and Domm, 1968;Ukeshima, 1994).…”
Section: Asymmetric Germ Cell Distribution In Female and Male Embryonmentioning
confidence: 99%
“…Another possible factor contributing to germ cells reduction in chicken embryonic ovaries is Intarapat and Stern: Gonadal Asymmetry in Chicken Embryos apoptosis of germ cells (Ukeshima and Fujimoto, 1991;Ukeshima, 1996;Van Nassauw et al, 1996). Previous studies reported that there are numerous spaces in the medulla of embryonic ovaries called "lacunae" in which dead oogonia are eliminated from both left and right medulla through the lacunae (Romanoff, 1960;Kannankeril and Domm, 1968;Ukeshima, 1994).…”
Section: Asymmetric Germ Cell Distribution In Female and Male Embryonmentioning
confidence: 99%